Ocorrência da infecção por Toxoplasma gondii por sorologia e PCR associado a fatores de risco em cães - Boa Sorte, Eveline da Cruz (2012)
Toxoplasmosis is a common infection in animals and humans, caused by Toxoplasma gondii configured as an important protozonosis. The dog has epidemiological importance to act as sentinel of infection in man. Seroepidemiological surveys of these animals are important tools for surveillance and disease control in health programs. Aiming to understand the occurrence of antibodies and to identify risk factors for infection with T. gondii in dogs, blood samples from 269 dogs were collected for the PCR and indirect immunofluorescence (IFA) found 48,7% of dogs in the serology reagents and 15,6% positivity in the PCR. Risk factors significantly associated (p < 0,05) serology, including race, age, street access and the type of flooring and the environment in which the animal lived. By having the role of guardians in toxoplasmosis, the high prevalence of infection with T. gondii in the areas studied dogs alert to the risk to public health in this region and the need to adopt strategies for prevention and control, including the actions of health education.